A comparative single-dose bioequivalence study of two Glibenclamide brands among healthy volunteers. (c2000) - Tannous, Elias Fouad (2000)
Glibenclamide is a second generation sulfonylurea oral hypoglycemic agent that plays an important role in the therapy of type II diabetes mellitus (DM-II); moreover. glibenclamide (Glibamid®) is being extensively used among diabetics in the middle east, including Lebanon where this drug is manufactured, without any clinical in vivo implication showing or confirming its bioequivalency. So, this investigation was carried out to evaluate the in vitro dissolution as well as the bioavailability and pharmacokinetic properties of two tablet oral dosage forms of glibenclamide, Daonil® (drug A) and Glibamid® (drug B) in a single dose of 5 mg among healthy volunteers. The two products were found to comply with the compendial requirments for both disintegration and content uniformity; moreover, the 111 vitro dissolution characteristics of the two products were similar. Method: Ten healthy male volunteers were enrolled in the study, each received a single dose of each drug in an open randomizes two-way cross-over study, with a wash out period of 7 days. Blood samples were obtained over a 10 hours interval according to this fashion: At zero, 0.5, 1, 1.5, 2, 2.5 , 3, 4, 5, 6, 8, and 10 hours. These samples were analyzed for serum glucose by the glucose oxidase method and glibenclamide by a sensitive HPLC assay. Results.· The two products were closely related in terms of their in vitro compendial requirements. Moreover, there was no significant difference with respect to peak serum concentration (103.92 ± 43.98 and 98.5 ± 51.26 nglml for products A and B, respectively) or to the corresponding peak times (2.6 ± 0.66 and 2.3 ± 0.88 hours for A and B respectively) . Furthermore, the difference between area under serum concentration-time curve (AUC) for the two products ( 390.86 ± 152.61 and 360.7 ± 160.21 ng hr Iml for A and B, respectively) was not statistically significant, with P > 0.05. The comparable serum glucose levels for the two products supported the pharmacodynamical equivalence between the two glibenclamide brands. Conclusion: The findings in this study indicates that the two products of glibenclamide are bioequivalent in terms of bioavailability and pharmacodynamic effect on healthy male volunteers.